Assessing the efficacy of herbal supplements for managing obesity: A comprehensive review of global clinical trials - Mahboobeh Ghasemzadeh Rahbardar; Gordon A Ferns; Majid Ghayour Mobarhan (Iranian Journal of Basic Medical Sciences, 2025)
Obesity remains a significant worldwide health concern, and further research into other strategies, including herbal weight-loss medications, is necessary. By reviewing clinical trials, this study aims to evaluate the effectiveness of herbal medicines for weight loss or obesity. A comprehensive search was conducted using multiple databases. Clinical trials evaluating the effects of herbal medicines on weight loss or obesity management were included. Relevant data, such as study design, intervention details, and outcome measures, were extracted and analyzed. The use of herbal medicines exhibited varying efficacy in promoting weight loss or managing obesity. Some herbal interventions significantly reduced body weight, body mass index (BMI), and waist circumference. Notably, these interventions led to decreases in fasting blood glucose (FBG) and homeostatic model assessment of insulin resistance (HOMA-IR), regulating insulin levels while increasing levels of catalase (CAT) and glutathione (GSH). Additionally, reductions in inflammatory markers such as high-sensitivity C-reactive protein (hs-CRP) and tumor necrosis factor-alpha (TNF-α) were observed, indicating a potential anti-inflammatory effect. Mechanisms of action included appetite regulation, fat oxidation, increased satiety, enhanced insulin sensitivity, and modulation of lipid metabolism. However, it is important to note that these herbal interventions’ efficacy and safety profiles may vary among different population groups. The findings suggest that certain herbal medicines hold promise as adjunctive therapies for weight loss and obesity management. However, comprehensive and targeted research efforts are warranted to determine these herbal interventions’ optimal use, dosages, and long-term effects in specific population subgroups.